Printed Nonfullerene Organic Solar Cells with the Highest Efficiency of 9.5%. Issue 13 (22nd January 2018) - Lin, Yuanbao; Jin, Yingzhi; Dong, Sheng; Zheng, Wenhao; Yang, Junyu; Liu, Alei; Liu, Feng; Jiang, Yufeng; Russell, Thomas P.; Zhang, Fengling; Huang, Fei; Hou, Lintao
Abstract: The current work reports a high power conversion efficiency (PCE) of 9.54% achieved with nonfullerene organic solar cells (OSCs) based on PTB7‐Th donor and 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐ d :2′, 3′‐ d ′]‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene) (ITIC) acceptor fabricated by doctor‐blade printing, which has the highest efficiency ever reported in printed nonfullerene OSCs. Furthermore, a high PCE of 7.6% is realized in flexible large‐area (2.03 cm 2 ) indium tin oxide (ITO)‐free doctor‐bladed nonfullerene OSCs, which is higher than that (5.86%) of the spin‐coated counterpart. To understand the mechanism of the performance enhancement with doctor‐blade printing, the morphology, crystallinity, charge recombination, and transport of the active layers are investigated. These results suggest that the good performance of the doctor‐blade OSCs is attributed to a favorable nanoscale phase separation by incorporating 0.6 vol% of 1, 8‐diiodooctane that prolongs the dynamic drying time of the doctor‐bladed active layer and contributes to the migration of ITIC molecules in the drying process. High PCE obtained in the flexible large‐area ITO‐free doctor‐bladed nonfullerene OSCs indicates the feasibility of doctor‐blade printing in large‐scale fullerene‐free OSC manufacturing. For the first time, the open‐circuit voltage is increased by 0.1 V when 1 vol% solvent additive is added, due to the vertical segregation of ITIC molecules during solvent evaporation. Abstract : Printed nonfullerene organic solar cells are investigated with a power conversion efficiency of 9.54% via incorporating a 1, 8‐diiodooctane additive for achieving a favorable nanoscale phase separation. The migration of nonfullerene acceptor molecules from bottom to top helps form the optimal donor/acceptor interface distribution, leading to the reduced exciton recombination and optimized electrical parameters.